Penerapan Tema Green Design pada Interior Sekolah Teologia Hosanna Mission Center di Manado - Prasetyo, Yonathan (Intra, 2013)
Theology school is a school that engaged in Christianity and aims to educate the students to be a God-fearing and could become a servant of God as an evangelist, teacher or have a soul, to feed the church later. While the Manado area, the majority of the Christian faith is a religion, which the teachings of the ancestors is already believe that the Lord Jesus Christ is the true Savior, so that up to now they are still hereditary inherited this belief, both in terms of the government to reach the public.The method used is the method of field studies and direct observations as well as literature, due to the direct observation we get to know the situation on the ground directly and with the literature we can find out what will be required in the design of this school.This design response to emerging issues in the tackle global warming problem, it will be made a theological school design green design concept in the design which will use the material or materials that are environmentally friendly, as well as the use of energy and resources efficiently, thereby also preserves the environment, in which we are living on this earth has the obligation to protect the environment around us.